Health-promoting phytochemicals: (1) in response to environmental factors in lettuce, spinach and tomato ; (2) development of 3D cell culture model for potential anticancer role - Xu, Jingwen (Kansas State University, 2018)
As health-promoting agents, phytochemicals are biosynthesized in the plants that typically respond to environmental stresses. This study focused on the analysis of phytochemical contents in vegetables in response to environmental changes of high tunnel and light spectra. A potential anticancer activity was further studied by developing a novel 3D cell culture model. Three specific studies were conducted as follows. Study 1: High tunnel production has been applied in mid-west for many years due to the advantages of extending growing season and increasing crop yield. Previous studies, however, showed high tunnel resulted in reduction of phenolic contents in vegetables. Therefore, the first study was to confirm the effect of high tunnel on phenolic contents in two varieties of lettuce (‘Two Star’ and ‘Red Fire’) and carotenoid contents in two varieties of tomatoes (‘Mountain Fresh’ and ‘Celebrity’). Phenolics in lettuce and carotenoids in tomato were isolated and quantitated, respectively, by HPLC. High tunnel resulted in a significant reduction of phenolic contents in ‘Two Star’ but not in ‘Red Fire’ lettuce when compared with open field. A significant decrease of carotenoid contents in ‘Celebrity’ but not in ‘Mountain Fresh’ tomato was also observed. Therefore, this study confirmed that high tunnel application reduced phenolic or carotenoid contents in one of the two lettuce or tomato varieties, suggesting the effect of high tunnel production is variable and genotype specific. Study 2: Light is an important environmental factor influenced not only photosynthesis but also phenolic biosynthesis in vegetables. The objective of this study was to investigate the effect of supplemental light spectra including red, far-red, and blue light on phenolic contents in two varieties of lettuce (green-leaf variety ‘Two Star’ and red-leaf variety ‘Red Fire’) and two varieties of spinach (‘Avon’ and ‘Bloomsdale’). The phenolics were extracted and quantitated by HPLC. Far-red and blue light but not red light resulted in an increase of phenolic contents in ‘Two Star’ lettuce. In ‘Red Fire’ lettuce, a significant increase in phenolic contents were observed when exposed to red light, while far-red and blue light reduced phenolic contents. Supplemental lighting did not alter flavonoid contents in two varieties of spinach. Taking together, the results showed that supplemental lighting and its spectral quality had significant effect on the phytochemical contents of lettuce but not spinach, and the impact varied depending upon the variety or species. Study 3: Traditionally, cancer research is primarily relied on in vitro 2D monolayer cell culture and in vivo animal model studies. Given a flat 2D cell culture that usually lacks 3D microenvironmental cell-cell interaction and considering an animal model that is typically expensive and time-consumed, an alternative 3D cell culture has been promising. This pilot study was to develop a novel 3D hydrogel cell culture model of human hepatocarcinoma HepG2 cells or colorectal adenocarcinoma SW480 cells by treating with chlorogenic acid (CGA) at 0-40 [mu]M. The results showed both HepG2 and SW480 cells grew much better in 3D hydrogel culture system than 2D by extended exponential phase and high proliferation. CGA treatment resulted in a dose- and time-response inhibition of HepG2 and SW480 growth in exponential phase, while HepG2 cells were more susceptible than SW480 cells. Establishment of this novel 3D hydrogel culture model for future phytochemical function may bridge the gap between 2D cell culture and in vivo animal model studies. Taken together, this dissertation of three studies focused on phytochemicals from quantitation analysis in vegetables in response to environmental factors of high tunnel and light spectra to a novel 3D hydrogel cell culture development for potential phytochemical anti-cancer function. The conclusions, i.e., (1). high tunnel application reduced phenolic or carotenoid contents in special genotype of lettuce or tomato varieties; (2). lighting and its spectral quality had significant effect on the phytochemical contents of lettuce but not spinach; (3). establishment of a novel 3D hydrogel culture model for phytochemical treatment may bridge the gap between 2D cell culture and in vivo animal model studies, could be of particular significance in health-promoting phytochemical research and functional food application.
Keywords: Phytochemicals; Environmental factors; Anti-cancer; HepG2 cell; SW480 cell; 3D hydrogel cell culture model